Comparative evaluation of salivary cortisol levels in bruxism patients before and after using soft occlusal splint: An in vivo study - Pudi Sriharsha; Anil Kumar Gujjari; M R Dhakshaini; Akila Prashant (Wolters Kluwer Medknow Publications, 2018)
Introduction: Bruxism is defined as a nonfunctional activity or a parafunctional habit characterized by the unconscious repetitive motion of clenching and/or grinding of the teeth. Soft occlusal splints have been considered as the first-line strategy for treating nocturnal bruxism. Cortisol is a major steroid hormone secreted by fascicular zone of the adrenal cortex, belonging to the glucocorticosteroidal group of hormones. Clinical studies have shown that when humans are placed under stress, the hypothalamic-pituitary-adrenocortical axis is activated, leading to an increase in cortical secretion. However, the effect of splint is questionable by some researchers, and best way to perceive the effect of soft splints in patients with bruxism is by evaluating the stress levels. Materials and Methods: A total of 20 individuals suffering from bruxism were selected from the Outpatient Department of Prosthodontics and Crown and Bridge, JSS Dental College and Hospital, Mysore. Saliva samples were collected before and after using the occlusal soft splints and subjected to enzyme-linked immunosorbent assay for determining the salivary cortisol levels. Results: The collected data were subjected to appropriate descriptive statistics, paired sample t-test, and one sample t-test. The paired sample t-test shows that intragroup comparison of the mean cortisol level in the study group shows near significant values, which means there is a decrease in the salivary cortisol levels in patients after using soft occlusal splint, but statistically nonsignificant. Conclusion: In the present study, it has been found that 70% of individuals after using the soft occlusal splint showed decreased cortisol levels.